Attitudes Toward Caring for Older Adults among Undergraduate Nursing Students at a Public University in Kuala Lumpur, Malaysia - Ismail, Azera Hasra; Hussein, Siti Zuhaida; Mohamed Yasi, Aslina; Ishak, Nurul Izzati; Mohd Yazar, Nurul Nazira; Sabri, Nur Syafiqah (UI Scholars Hub, 2023)
Background: The growing number of elderly members of the population is expected to increase the demand for more dedicated nursing students committed to providing excellent care. This study aims to determine prevailing attitudes toward the care of older adults among undergraduate nursing students at a public university in Kuala Lumpur, Malaysia. Methods: This is a quantitative cross-sectional survey of 107 undergraduate nursing students enrolled at a public university in Kuala Lumpur, Malaysia. The students were recruited using stratified random sampling. The respondents’ attitudes toward caring for older adults were measured using 14 items from the Geriatrics Attitudes Scale Survey Questionnaire. Data were analyzed using IBM® SPSS® Statistic V.26.0, in which p < 0.05 was statistically significant. Results: The mean total score of attitudes was 46.64 (SD = 4.87), and 88.2% of respondents had a positive attitude. A significant relationship was observed between attitudes toward caring for older adults and years of study (p = 0.015, U = 10.416). Conclusions: The majority of undergraduate students had positive attitudes toward caring for older adults. Early clinical practice and geriatric education are needed to ensure that older adults will receive the best and most efficient care and treatment in the future.